Smart specialisation and hydrogen: a European innovation policy for market transition. - Bogdzinski, H.; Wedemeier, J. (Innovation: The European Journal of Social Sciences, 2025)
This paper examines the growing significance of hydrogen within the European Structural and Investment Funds (ESIF) programmes and smart specialisation strategies, particularly in the context of the EU's decarbonisation agenda and recent geopolitical developments. Using a mixed-methods approach, the study analyses investment trends, policy priorities, and the role of scientific domains in advancing hydrogen technologies. Key findings reveal that hydrogen and renewable energy have become central to smart specialisation strategies. By comparing two funding periods (2013–2020 and 2021–2027), the paper demonstrates substantial investments in the latter period. The research highlights hydrogen's potential to transform energy-intensive industries, such as steel and petrochemicals, while identifying the prioritisation of specific regions as a catalyst for building a hydrogen economy. However, achieving these objectives requires a more targeted and robust implementation of smart specialisation priorities. The paper concludes that enhanced policy frameworks are essential for realising the EU's ambitious net-zero targets, making hydrogen a cornerstone of the European energy transition.